2017
DOI: 10.1590/s0100-204x2017000800006
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of production and seed variables to the genetic divergence in passion fruit under different nutrient availabilities

Abstract: -The objective of this work was to evaluate the relative contribution of variables related to fruit production and to seed morphophysiological characteristics to the genetic divergence in passion fruit (Passiflora edulis) progenies, aiming at selecting progenies potentially responsive to fertilization. Ten progenies were evaluated under conditions of low (50% of the recommended dose of fertilizers) and high soil fertility (dose 50% higher than the recommended one), regarding variable sets related to production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The clustering of FSFs into four different groups based on physical and physiological seed traits indicates the existence of genetic variability between the genotypes and, consequently, their potential for selection. Similar results were described in studies evaluating seed traits in different passion fruit genotypes (Marostega et al 2017, Rodrigues et al 2017, Rosado et al 2017, Torres et al 2019.…”
Section: Discussionsupporting
confidence: 85%
“…The clustering of FSFs into four different groups based on physical and physiological seed traits indicates the existence of genetic variability between the genotypes and, consequently, their potential for selection. Similar results were described in studies evaluating seed traits in different passion fruit genotypes (Marostega et al 2017, Rodrigues et al 2017, Rosado et al 2017, Torres et al 2019.…”
Section: Discussionsupporting
confidence: 85%
“…Cerqueira -Silva et al (2009) evaluated intra-and interspecific genetic dissimilarity between genotypes of P. edulis and P. setacea via physicochemical descriptors -interspecifically, mainly -and found variability between the genotypes. Rodrigues et al (2017) also observed groups of passionfruit progeny formed by the UPGMA method at three fertilization levels, in an evaluation of seed and yield variables. The progeny were clustered distinctly at the different fertilization levels, and the variables seedling length and germination speed index were positively correlated with number of fruits, pulp weight, and fruit weight in lower nutrient-availability conditions.…”
Section: Sj % Valuementioning
confidence: 89%
“…Other possibilities could relate to genetic diversity among the groups, since passion fruit flowers are known to be primarily inbreeding but up to 70% outcrossing (Bruckner et al, 1995), crosses between low and high germination genotypes are needed. Seed quality can also relate to plant physiological differences during fruit production (Carvalho and Nakagawa, 2012;Lima et al, 2017;Fischer et al, 2018). Genebank accessions were briefly stored prior to the tests so some difference with landraces could be due to seed age (Larré et al, 2007).…”
Section: Discussionmentioning
confidence: 99%